Bifid mandibular condyle. (6th November 2012) - Katti, Girish; Najmuddin, Mohammed; Fatima, Syeda; Unnithan, Jayesh
Abstract : A 20-year-old young male patient presented with limited mouth opening and cosmetic disfigurement since childhood. On examination, marked mandibular hypoplasia resulting in a convex facial profile was noted. Further radiographic investigation using orthopantomograph and CT scan with three-dimensional reconstruction revealed bifid mandibular condyle of the right side.